Identifikasi Postur Kerja Menggunakan Metode Rapid Entire Body Assesment (REBA) terhadap Keluhan Muscoluskeletal Disorder Pada Pekerja Kuli Panggul Kilang Jagung di Desa Balai Kasih Langkat: Penelitian - Cut Saura Salmira; Nur Amalia; Dilla Fitria (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
Ergonomics plays a crucial role in improving occupational safety and health. Ergonomics is implemented through the design of work systems to reduce thigh pain and stress on the skeleton and muscles. Designing workstations with visual displays also aims to minimize eye discomfort and body posture, while ergonomic work tools help reduce worker fatigue. This type of work carries a high risk of musculoskeletal disorders (MSDs) due to non-ergonomic work postures and repetitive movements. Lack of application of ergonomic principles can increase the risk of musculoskeletal injuries. This study aims to determine the relationship between work posture and MSD complaints among corn porters in Balai Kasih Village. This 2025 study used a descriptive analytical design with a cross-sectional approach. The population consisted of 32 workers, with 27 samples selected using purposive sampling. Data were collected through the Rapid Entire Body Assessment questionnaire and the Nordic Body Map to identify body parts experiencing complaints. Analysis was performed univariately and bivariately using the Chi-Square test. The results of the study showed a significant relationship between work posture and MSD complaints (p-value = 0.000).